Philosophy of Autonomous Science: Ten Questions for the Coming Age of Artificial Scientists. - Krenn, Mario; Champion, Heather (Daedalus: Journal of the American Academy of Arts & Sciences)
Artificial intelligence is beginning to make remarkable contributions in science, from protein design to materials discovery and experiment design. Yet we believe that moving from powerful tools to autonomous scientists is not just a technical challenge but also a deep philosophical and conceptual one. For that reason, we argue for a Philosophy of Autonomous Science (PAS) : a program that translates core epistemic aims, including understanding, curiosity, surprise, interest, creativity, and novelty, into computable, nonanthropocentric objectives, while ensuring the safe and successful deployment of artificial scientists. Drawing on our own research experience, we show how insights from the philosophy of science can directly inform the design of AI systems for scientific discovery; outline ten inaugural questions that define the agenda of PAS; and invite philosophers, scientists, and AI researchers to collaborate in shaping the principles of the coming era of artificial scientists.